Induction of Interleukin-6 Trigger an Apoptosis Through Il-17 and Stat3 Pathway that Alleviated by Phycocyanin Treatment - Haryanti, Elizabeth; Gondo, Harry K (Universitas Wijaya Kusuma Surabaya, 2016)
This study was to analyze the optimum dose of IL-6 induction in pregnant rats that could trigger an increase in mean arterial pressure and protein as two symptoms of preeclampsia. A total of 25 pregnant rats was divided into 5 groups, including pregnant rats the control group (without induction of IL-6), a group of pregnant rats were given an induction in IL-6 doses of 1.25 ng/day, a group of pregnant rats given doses of IL-6 induction 2.5 ng/day, a group of pregnant rats were given an induction of IL-6 doses of 5 ng/day, and groups of pregnant rats were given an induction in IL-6 doses of 10 ng/day. Induction of IL-6 was performed on the tenth day of gestation for 5 days. The expression of caspase-3, IL-17, and STAT3 were analyzed by confocal laser scanning microscopy. The expression of caspase-3, IL-17 and STAT3 was significantly higher in preeclampsia group than the control group (p<0.05). The expression of caspase-3 decreased significantly in all groups were treated by phycocyanin compared to the preeclamptic group (p<0.05), but has not been able to reach expression comparable to the control group (p<0.05). Expression of IL-17 decreased significantly in the group given the two highest doses of phycocyanin compared to the preeclampsia group (p<0.05). STAT3 expression decreased significantly in all groups were treatedby phycocyanin compared to the preeclamptic group (p<0.05), reached expression comparable to the control group in the group received phycocyanin at doses of 10 and 20 ng (p> 0.05). In conclusion, IL-6 on pregnant rats were able to increase apoptosis through IL-17 and STAT pathway. Inhibition of apoptosis due to phycoyanin treatment not only involve the formation of IL-17, this data is found in phycocyanin doses of 10 and 20 ng.